Effect of PBL Model with Liveworksheets on Student Activity and Biology Learning Outcomes - Harahap, Nurhasanah; Djulia, Ely; Manurung, Marni (Biology Teaching and Learning, 2025)
Abstract. This study aims to determine the effect of the Liveworksheets-assisted Problem Based Learning model on biology learning activities and outcomes. This study uses a Quasi-Experimental method with a Pretest-Posttest group design. The sample used was class XI-1 as the experimental class and class XI-2 as the control class. Data collection techniques were through tests (pretest and posttest) to measure learning outcomes and observation sheets to measure student learning activities. The results showed that the Liveworksheets-assisted Problem-Based Learning model had an effect on student learning activities and outcomes in the human movement system material in class XI at SMA Negeri 1 Tebing Syahbandar. An increase in student learning activities can be seen in meeting 1 at 62.6%, meeting 2 at 77.27%, and meeting 3 at 81.82% in the very active category. The increase in student learning outcomes can be seen from the average biology learning outcome score of the experimental class, which was 80, higher than that of the control class, which was 68.83. The results of the Independent Sample t Test showed a significance value < a (0.05), namely 0.000 < 0.05, so H0 was rejected and Ha was accepted. This means that there is an effect of the Problem-Based Learning model assisted by Liveworksheets.Keywords: problem based learning model, liveworksheets, learning activities, learning outcomes.